Marital dissolution of Filipino males reasons, life challenges and coping strategies - Agustin, Ma. Carmela De Luna
This phenomenological research studied the experience of marital dissolution from the perspective of Filipino males. It enumerated the reasons for marital dissolution, identified the life challenges experiences after the break-up, and described the coping strategies used by the Filipino males in adjusting to marital dissolution. A sample comprised of six Filipino males residing in Quezon City was obtained through snowball sampling. Written in-depth interviews were used for data collection. Data collected were analyzed using thematic tables that led to the formulation of themes for the reasons, life challenges and coping strategies of the participants. Ten themes emerged for the reasons namely: meddling outsiders, infidelity, mistrust, dominant wife, wounded pride of husband, shortcomings of the wife, "unwifely" behavior, conflict with work, constant bickering, and overload of responsibilities. Five themes emerged for life challenges namely: reactions and feelings after separation, longing for a companion, relating with relatives and former in-laws, relating with their children and positive life changes. Eight themes emerged for the coping strategies namely: blamed wife, accepted the situation, having a "kailangan magpakatatag" mindset, redirection, thought of and prioritized children, social support, attended seminars and read books, and finding new love. Future researches may consider a bigger sample size across socio-economic status in urban and rural areas, and comparing the impact of marital dissolution between males and females as well as between males with and without children, and on the children of the separated couples.